PELATIHAN SENAM KAKI DIABETES UNTUK PENCEGAHAN KOMPLIKASI PADA LANSIA - Cindy Aulia Rachelli; Sumarti Endah Purnamaningsih Maria Margaretha; Iswanti Purwaningsih; Elisabeth Iswantiningsih (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2025)
Diabetes mellitus is a non-communicable disease that often leads to chronic complications, particularly foot complications that may reduce independence and quality of life among the elderly. One preventive strategy to reduce diabetic foot complications is diabetic foot exercise, which aims to improve blood circulation, joint flexibility, and foot muscle strength. This community service activity aimed to improve the knowledge and skills of elderly people in performing diabetic foot exercises independently in Village Mangir Lor. A descriptive-participatory approach was applied through initial observation, education, demonstration, repeated practice, and evaluation. The participants consisted of six elderly individuals with diabetes mellitus. Diabetic foot exercise training was conducted three times per week for 20–30 minutes using simple media in the form of newspapers. Evaluation was carried out qualitatively by observing participants’ practical skills, participation, and enthusiasm. The results indicated an improvement in participants’ knowledge and ability to perform diabetic foot exercises independently, along with high levels of participation. This activity has the potential to serve as a preventive effort to reduce diabetic foot complications and is recommended for sustainable implementation in community settings.